Modeling of fluorescence line-narrowed spectra in weakly coupled dimers in the presence of excitation energy transfer - Lin, Chen; Reppert, Mike; Feng, Ximao; Jankowiak, Ryszard J. (My University, 2014)
This work describes simple analytical formulas to describe the fluorescence line-narrowed (FLN) spectra of weakly coupled chromophores in the presence of excitation energy transfer (EET). Modeling studies for dimer systems (assuming low fluence and weak coupling) show that the FLN spectra (including absorption and emission spectra) calculated for various dimers using our model are in good agreement with spectra calculated by: (i) the simple convolution method and (ii) the more rigorous treatment using the Redfield approach [T. Renger and R. A. Marcus, J. Chem. Phys.116, 9997 (2002)]. The calculated FLN spectra in the presence of EET of all three approaches are very similar. We argue that our approach provides a simplified and computationally more efficient description of FLN spectra in the presence of EET. This method also has been applied to FLN spectra obtained for the CP47 antenna complex of Photosystem II reported by Neupane et al. [J. Am. Chem. Soc.132, 4214 (2010)], which indicated the presence of uncorrelated EET between pigments contributing to the two lowest energy (overlapping) exciton states, each mostly localized on a single chromophore. Calculated and experimental FLN spectra for CP47 complex show very good qualitative agreement.
Keywords: Fluorescence line-narrowed (FLN) spectra; Excitation energy transfer; Weakly coupled chromophores; Chromophores